2022
DOI: 10.1021/acsenergylett.2c00167
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for the Formation of C2+ Products under Alkaline Conditions during the Electrochemical Reduction of CO2

Abstract: Establishing how Cu facilitates the electrochemical CO 2 reduction reaction (CO2RR) to C 2+ products remains a critical challenge. Under typical reaction conditions, the pH near the electrode is considerably more alkaline than that in the bulk due to mass transport limitations. Challenges with probing alkaline pathways using computational methods have limited understanding of the CO2RR under experimentally relevant conditions. In this work, using the Volmer reaction on Cu (100), we demonstrate that predicted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 78 publications
1
55
0
Order By: Relevance
“…conditions on Cu(100) and predicted that high overpotentials favor *COH formation while low overpotentials favor *CHO formation. 24 The same authors further suggested that CO dimerization likely dominates C−C bond formation steps. 24 The above-mentioned theoretical studies all used various pure DFT approximations, which suffer from electron selfinteraction error and incorrect frontier−orbital or band gaps, resulting in spuriously facile charge transfer.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…conditions on Cu(100) and predicted that high overpotentials favor *COH formation while low overpotentials favor *CHO formation. 24 The same authors further suggested that CO dimerization likely dominates C−C bond formation steps. 24 The above-mentioned theoretical studies all used various pure DFT approximations, which suffer from electron selfinteraction error and incorrect frontier−orbital or band gaps, resulting in spuriously facile charge transfer.…”
mentioning
confidence: 95%
“…24 The same authors further suggested that CO dimerization likely dominates C−C bond formation steps. 24 The above-mentioned theoretical studies all used various pure DFT approximations, which suffer from electron selfinteraction error and incorrect frontier−orbital or band gaps, resulting in spuriously facile charge transfer. 25 This is worrisome for modeling heterogeneous (electro)catalysis; 26−28 with respect to the particular electrocatalyst of interest here, pure DFT does not even correctly predict the adsite preference of the key catalytic intermediate (*CO) in CO 2 R on Cu surfaces.…”
mentioning
confidence: 98%
See 3 more Smart Citations